The Influence of Job Satisfaction on Intention to Stay Through Organizational Commitment As A Mediation Variable - Khoiruman An Nidhom; Nazaruddin Malik; Titiek Ambarwati (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to determine the effect of job satisfaction on the intention to stay through organizational commitment as a mediating variable. The population used in this study was the English village teacher or tutor LC Pare Kediri. The type of research data used is quantitative data and the source of data in this study is primary data. Research data collection through questionnaires. The data analysis method of this research is scale range and path analysis. The calculation of the range of job satisfaction scales shows good results, intention to stay shows high results, and organizational commitment shows high results. Job satisfaction has a positive effect on the intention to stay of the English village teacher LC. Job Satisfaction has a positive effect on organizational commitment English village teacher LC Pare. Organizational commitment has a positive effect on the intention to stay of the English village teacher LC Pare. Organizational Commitment does not mediate the effect of Job Satisfaction on the intention to stay English village teacher LC Pare. This study aims to determine the effect of job satisfaction on the intention to stay through organizational commitment as a mediating variable. The population used in this study was the English village teacher or tutor LC Pare Kediri. The type of research data used is quantitative data and the source of data in this study is primary data. Research data collection through questionnaires. The data analysis method of this research is scale range and path analysis. The calculation of the range of job satisfaction scales shows good results, intention to stay shows high results, and organizational commitment shows high results. Job satisfaction has a positive effect on the intention to stay of the English village teacher LC. Job Satisfaction has a positive effect on organizational commitment English village teacher LC Pare. Organizational commitment has a positive effect on the intention to stay of the English village teacher LC Pare. Organizational Commitment does not mediate the effect of Job Satisfaction on the intention to stay English village teacher LC Pare.